EXPERIMENTAL STUDY ON THE STRENGTH DEVELOPMENT ON CONCRETE BY PARTIAL REPLACEMENT OF COARSE AGGREGATES BY WASTED TRUCK TYRE PIECES - HavanjeDinakar, Raghavendra Prasad; Pavan; Gadgihalli, Vishal; Ramesh (International Journal of Research -GRANTHAALAYAH, 2017)
Wasted Truck Tyres can be used as an alternative for concrete coarse aggregate. The used tyres of truck are properly cutted and different ratios can be added to concrete blocks. The main components of modern tyres are synthetic rubber, natural rubber, fabric and wire, along with carbon black and chemical compounds. In the present paper, Truck Tyres are used as conventional coarse aggregate in concrete for high strength (M50 Grade) concrete for every incremental of 25% replacement up to 100% is done. Slump cone test, Vee-Bee consistometer test and Compaction factor test are conducted to find freshness of concrete. The concrete is casted in cubes to harden it, tests such as compressive strength, cylinders for split tensile strength and prisms for flexural strength for 7days, 14days and 28days curing are done. The results obtained are compared with conventional coarse aggregate (0% replacement) concrete.